(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the risk factors for reintubation in patients admitted to the intensive care units at the Regional University Hospital of Campos Gerais. Method: A prospective and observational study with the participation of 90 patients, based on clinical parameters for ventilatory weaning and possible complications. Data were analyzed using Kolmogorov-Smirnov and Shapiro-Wilk tests. For analysis and presentation of central tendency and dispersion measures, median, percentage, and interquartile range were chosen. The Mann-Whitney test was used for comparison between groups. The association of the sepsis variable between groups was presented in simple and relative frequency and compared using the chi-square test Results: As results, we found that 79 (87.7%) had successful extubation and 11 (12.2%) failed. Furthermore, sedation time was significantly longer in reintubated patients (p=0.009). Although not statistically significant, a positive fluid balance and the presence of sepsis were also factors suggestive of extubation failure. Conclusion: With these findings, it can be observed that the days of sedation were significantly longer in patients who were reintubated, and although there were no significant differences, the positive fluid balance and the presence of sepsis may also be suggestive of extubation failures.